Taking multi-sector dynamic general equilibrium models to the data - Huw Dixon; Engin Kara (Cardiff University, Cardiff Business School, 2012)
We estimate and compare two models, the Generalized Taylor Economy (GTE) and the Multiple Calvo model (MC), that have been built to model the distributions of contract lengths observed in the data. We compare the performances of these models to those of the standard models such as the Calvo and its popular variant, using the ad hoc device of indexation. The estimations are made with Bayesian techniques for the US data. The results indicate that the data strongly favour the GTE.
Keywords: E32; E52; E58; 330; DSGE models; Calvo; Taylor; price-setting